Critical barriers in implementing reverse logistics in the Chinese manufacturing sectors - Abdulrahman, Muhammad D.; Gunasekaran, Angappa; Subramanian, Nachiappan (Elsevier, 2014)
Reverse logistics (RL) is gaining momentum worldwide due to global awareness and as a consequence of resource depletion and environmental degradation. Firms encounter RL implementation challenges from different stakeholders, both internally and externally. On the one hand, various governmental agencies are coming out with different environmental regulations while on the other hand academics and researchers are contributing solutions and suggestions in different country contexts. In a real sense however, the benefits of RL implementation is not yet fully realized in the emerging economies. This paper proposes a theoretical RL implementation model and empirically identifies significant RL barriers with respect to management, financial, policy and infrastructure in the Chinese manufacturing industries such as automotive, electrical and electronic, plastics, steel/construction, textiles and paper and paper based products. Key barriers from our study, with respect to these four categories, are: within management category a lack of reverse logistics experts and low commitment, within financial category a lack of initial capital and funds for return monitoring systems, within policy category a lack of enforceable laws and government supportive economic policies and, finally, within infrastructure category a the lack of systems for return monitoring. Contingency effect of ownership was carried out to understand the similarities and differences in RL barriers among the multinational firms and domestic firms investigated.